Clinical observation of sleep therapy instrument in the treatment of sleep disorders in the elderly (睡眠治疗仪辅助治疗老年睡眠障碍临床观察) - WU Nian (吴念); NING Huifen (凌慧芬); CHEN Xi (陈曦) (中西医结合护理)
Objective To observe the effect of sleep therapy instrument in the treatment of sleep disorders in the elderly. Methods Totally 120 elderly patients with insomnia were divided into control group and observation group, with 60 patients in each group. The control group was given routine mind-body therapies, including psychological implications, relaxation therapy, exercise therapy, etc. On this basis, the observation group used Beethoven sleep therapy instrument for adjuvant treatment. Comprehensive Assessment of elderly patients with sleep disorders, Pittsburgh Sleep Quality Index Scale (PSQI ), Self-rating Anxiety Scale (SAS) , Geriatric Depression Scale (GDS-15) were used for comprehensive evaluation. Results The PSQI score, SAS score, GDS-15 score decreased in both two groups after intervention, and PSQI score, SAS score, GDS-15 score in the observation group were lower than those in the control group, with significant difference (P＜0. 01). Conclusion Based on the routine physical and psychological therapy, application of sleep therapy instrument is more effective in the treatment of sleep disorders in the elderly. (目的 探讨睡眠治疗仪辅助治疗老年睡眠障碍的效果。方法 选取2019年1月—2020年1月医院收治的老年睡眠障碍患者120例, 分为对照组和观察组, 各60人。对照组给予常规身心疗法干预, 包括心理暗示、放松治疗、运动治疗等, 观察组在对照组基础上采用贝多芬睡眠治疗仪进行辅助治疗。对老年睡眠障碍患者进行老年综合评估, 采用匹兹堡睡眠质量指数量表(PSQI)、焦虑自评量表(SAS)和老年抑郁量表(GDS-15)进行综合评估。结果 治疗后, 2组PSQI评分、SAS评分、GDS-15评分均较干预前下降, 且观察组PSQI评分、SAS评分、GDS-15评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 在常规干预的基础上, 应用睡眠治疗仪能有效改善老年睡眠障碍患者睡眠质量。)